Pemertahanan Bahasa Bali Melalui Gamelan Gambang - I Nyoman Mariyana; Gek Diah Desi Sentana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Language as a communication tool consisting of a symbol system, which is composed of the framework of social group relations, can also have an impact on the overall structure of cultural interaction. Art as one of the cultural activities in Bali, can not be separated from the use of the Balinese language as a medium of communication. In Balinese gamelan practices, the role of the Balinese language is very important. This can be seen from the activity of playing gamelan Gambang. Gamelan Gambang is one of the unique Balinese gamelan. In which there is the use of the Balinese language as a form of maintaining the Balinese language from generation to generation. The method used in this study uses descriptive qualitative research methods through data collection, observation, interviews, discography, and documentation. Through this method, it is known that the preservation of the Balinese language is carried out by using the Balinese language alus as verbal communication, introduction to prayers of praise, writing Gambang gending notation. Various terms in Balinese gamelan techniques that use Balinese, such as the terms kotekan, cecandetan, tetorekan and oncang-ocang, while in terms of the terms of the playing techniques of each Gambang instrument that uses Balinese, namely; noltol, nyelangkit, nyelat/nyelag, ngoncang and nyading.